STRATEGI DAN PERFORMA PROGRAM KOMPAS TV DALAM MENGHADAPI PERSAINGAN TV BERITA PADA PILPRES 2019 - Ebnu Yufriadi (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2019)
This research examined the program strategy and program performance of Kompas TV as a newcomer to the news TV channel in Indonesia during the 2019 presidential election (pilpres 2019). Kompas TV faces heavy competition against other news channels that have more diverse and varied programs. The research analyzed the available data supported by a number of theories and expected to be a guideline to the content selection for Kompas TV. The research focused on the program strategy of Kompas TV as a market challenger to Metro TV as a pioneer of news television in Indonesia, as well as the program performance of Kompas TV. This research used program strategy theories by Peter Pringle. Descriptive qualitative methods are applied in this research by (1) using a list of questions; (2) interviewing research and data mining managers and news executive producer of Kompas TV; (3) using secondary research such as books, journals, printed articles, and online sources. The researcher makes an answer by analyzing the collected data. The program strategy of the Kompas TV was interesting to be analyzed considering the positive results where the rating and share of Kompas TV were better than Metro TV during the 2019 presidential election.